Intestinal Parasitosis and CD4 Levels among Cancer Patients in Calabar, Nigeria (African Journal of Biomedical Research, 2022)
Cancer is a public health menace with high rate of mortality, especially in developing countries. The condition as well as its therapy may negatively affect the immune system of its patients thereby predisposing them to opportunistic infections, including parasitic diseases with management problems. To investigate the intestinal parasite status and CD4 levels of cancer patients visiting a Tertiary Hospital, in Calabar, Nigeria, hence proffer solution to the cancer management problems. A cross sectional [study design was employed with 317 stool and blood samples, each collected from 186 confirmed cancer and 131 non-cancer patients (apparently healthy individuals). Direct microscopy and formol ether concentration techniques were employed for the examination and identification of stool parasites. BD-fascount technique for CD4 count. Data were analyzed with statistical package for social sciences (SPSS) version 25.0 using Chi-square and t-test, respectively at P < 0.05 and 95% confidence interval. The overall prevalence of intestinal parasites in this study was 87(27.44%) with significantly higher prevalence seen in cancer 65(34.9%) than in non-cancer subjects 22(16.8%), (X2 =12.72, P